2017
DOI: 10.1007/s12094-017-1686-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ovarian cancer type I and type II microenvironment on the phenotype and function of monocyte-derived dendritic cells

Abstract: PURPOSEThe aim of this study was to evaluate the influence of ovarian cancer cell lysates isolated from type I or type II ovarian cancer (OC) on the phenotype of monocyte-derived dendritic cells (Mo-DCs) and the cytokine profile. We also determined whether the Mo-DCs and tumor microenvironment, reflected by peritoneal fluid (PF) from type I or II ovarian cancer, could promote regulatory T cell (Tregs) differentiation from naive CD4+ lymphocytes in vitro.RESULTSOur results show a significant role of the ovarian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
1
5
1
Order By: Relevance
“…In contrast, type II contains mostly high-grade undifferentiated and serous carcinomas which evolve rapidly and are strongly aggressive. 35,36 Although we observed the tendency to elevate MSLN concentrations in type II compared with type I, the differences were not statistically significant. Our results confirm previous observations that MSLN was secreted to the circulation by the mesothelial cells of the peritoneum affected by the tumor cells.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…In contrast, type II contains mostly high-grade undifferentiated and serous carcinomas which evolve rapidly and are strongly aggressive. 35,36 Although we observed the tendency to elevate MSLN concentrations in type II compared with type I, the differences were not statistically significant. Our results confirm previous observations that MSLN was secreted to the circulation by the mesothelial cells of the peritoneum affected by the tumor cells.…”
Section: Discussioncontrasting
confidence: 65%
“…41 We have also shown that monocyte-derived dendritic cells (Mo-DCs) generated from type II Kurman and Shih of OC secreted higher levels of IL-10 compared to the cells collected from women with type I. 36 It seems probable that substantial reversal of immunosuppression can be realized by blocking IL-10 in the TME, which may allow to increase cytotoxicity of MSLN-engrafted CAR T cells and enhance the potential for their using in clinical practice. It is worth noting that previous results demonstrated that tumor cells undergo MSLN/CA125-dependent cell adhesion in the mesothelial cells of peritoneum and confirmed that MSLN and CA125 mediate cell attachment.…”
Section: Discussionmentioning
confidence: 99%
“…All of above events lead to “perfect storm” ideally suited to tumor immune escape to create metastasis-promoting TIME. Additionally, current data indicate that PF-derived mediators may play an important role in immune modulation of EOC milieu and seem to be one of the most likely players for MDSC-mediated support of tumor growth, which is not surprising, given that our previous work indicates that numerous factors are involved in the formation of ascites and promote dissemination of EOC cells (9, 49, 50). Indeed, it may be reasonable to consider the use of inhibitors against PF-derived immunosupressive mediators to restrain cancer metastasis.…”
Section: Discussionsupporting
confidence: 60%
“…In the light of our previous findings about intercellular communication in EOC driven by complex/dynamic network of immunosupresive mediators we examined pivotal MDSC-related factors (9, 1113, 21). Indeed, we demonstrated that level of TGF-β in the plasma positively correlate with the frequency of ARG + M-MDSCs in the PF.…”
Section: Discussionmentioning
confidence: 99%
“…The aims of this study were to (1) characterize the physical properties of EBVaGC exosomes, (2) identify their physiological effects on dendritic cell maturation in vitro, and (3) evaluate dendritic cells in EBVaGC in vivo. In the present study, we employed the use of dendritic cell markers suitable for immunohistochemical analysis as previously reported [ 11 ] to visualize tumor-associated dendritic cells (TA-DCs) and bridge findings from the flow cytometry analysis of gastric cancer-derived exosomes with those of the immunohistochemical analysis of gastric cancer tissues; the dendritic cell markers we used include CD1a, which is a marker for immature monocyte-derived DCs (moDCs), CD83 and CD86 for mature or activated DCs [ 12 ], and other markers (S100, Langerin, and BDCA-2). The maturation of moDCs was considerably suppressed in EBVaGC, which might have been mediated through the excretion of exosomes from the neoplastic cells infected with EBV.…”
Section: Introductionmentioning
confidence: 99%